Health system performance for multimorbid cardiometabolic disease in India: a population-based cross-sectional study - Geldsetzer, Pascal; De Neve, Jan-Walter; Mohan, Viswanathan; Prabhakaran, Dorairaj; Roy, Ambuj; Tandon, Nikhil; Davies, Justine I.; Vollmer, Sebastian; Bärnighausen, Till; Prenißl, Jonas (Global heart, 2022)
Article: Health System Performance for Multimorbid Cardiometabolic Disease in India: A Population-Based Cross-Sectional Study
Gesehen am 08.04.2022